Open Data and Data Analysis Preservation Services for LHC Experiments. Issue 3 (December 2015) - Cowton, J; Dallmeier-Tiessen, S; Fokianos, P; Rueda, L; Herterich, P; Kunčar, J; Šimko, T; Smith, T
Abstract: In this paper we present newly launched services for open data and for long-term preservation and reuse of high-energy-physics data analyses based on the digital library software Invenio. We track the "data continuum" practices through several progressive data analysis phases up to the final publication. The aim is to capture for subsequent generations all digital assets and associated knowledge inherent in the data analysis process, and to make a subset available rapidly to the public. The ultimate goal of the analysis preservation platform is to capture enough information about the processing steps in order to facilitate reproduction of an analysis even many years after its initial publication, permitting to extend the impact of preserved analyses through future revalidation and recasting services. A related "open data" service was launched for the benefit of the general public.